Bucket List - Schreyer, Karmel (NewYork Cambridge University, 2014)
What things do you want to do before you die? How can you make sure your life is never boring? Create a bucket list ! This reader explores the most exciting, unusual, and sometimes crazy ways to build this list.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Upper-intermediate level